Scurvy: A Case Report - Eka Sri Rahayu; Mardy Pangarungan (HM Publisher, 2021)
Scurvy is a rare case found in many countries, but it is often found in refugee areas, especially in Africa. Vitamin C deficiency varies based on season and occurs more in men with age. The purpose of this research is to avoid misdiagnosis so that it can be a reference in the field of medicine to diagnose and provide management on scurvy. This prospective research was conducted with one sample of research. Observation had been carried out for two months, starting at one month after the patient was suspected with the diagnosis of scurvy. Computer Tomography (CT) Scan lumbosacral to pelvic results were normal. Laboratory test of HB result was 9.5 g/dl, in which MCV was 63.2 fL, MCH was 20.3 pg, and MCHC was 32.1 g/dl. Scurvy treatment in the first visit was 3x1 tablets vitamin C, 3x5 ml ibuprofen Syr, and physiotherapy. The results were that the patient still suffered swollen and bleeding gums, but the pain no longer existed, pale, behavioural disorders, unable to walk, and pain in both knees. After the second visit, the child got therapy of 4x50 mg vitamin C, 1x1 tablets vitamin B12, 1x150 IU vitamin E, 1x1 tablets cavit D3, and physiotherapy. After two weeks of treatment, there were no complaints of swelling, painful or bleeding gums. The child could straighten her legs, but she was still unable to walk due to the trauma of feeling great pain while walking. Special attention is required to diagnose appropriately so the doctor can minimize and prevent complications.